Are we what we do? Exploring group behaviour through user-defined event-sequence similarity. (July 2014) - Vrotsou, Katerina; Ynnerman, Anders; Cooper, Matthew
The study of human activity in space and time is an inherent part of human geography. In order to perform such studies, data on the time use of individuals, in terms of sequence and timing of performed activities, are collected and analysed. A common assumption when analysing individuals' time use is that groups that exhibit similar background and demographic characteristics also display similarities in how they use their time to structure their daily lives. In this article, we set out to investigate the correctness of such assumptions. We propose a visual analytics process based on sequence similarity measures tailored to event-based data such as performed activity sequences. The process allows an analyst to retrieve similarly behaving records according to user-selected similarity preferences and interactively explore aspects of this similarity in a multiple linked-view environment.